Pricing to equate environmental sanitation services, in the city of Sousa, in the State of Paraíba, Brazil - Assis, Lilian Figueirôa de; Vieira, Allan Sarmento; Olivera, Marcos Macri (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The objective of this work was to propose a method to calculate and equate the tariffs for the environmental sanitation services of the Department of Water, Sewage and Environmental Sanitation (DAESA) of the city of Sousa-PB, using an accounting-financial approach. It adopted the deductive method, is classified as exploratory, descriptive and documentary type, presents a case study and used a quantitative approach. Based on the data presented by DAESA: monthly consumption, operating costs, number of supply links by type of user and sewage connections, among others, an analysis was adopted considering cost-volume-profit, referring to cost accounting, so that this methodology could provide a basis for updating existing tariffs, by means of percentage corrections thereto. In order to meet the calculated Economic Break-Even Point (PEE ), the amounts should be adjusted by 74.9%, generating revenue of R 555,397.81, to cover R 82,335.40 of fixed costs and expenses and amortization of R 261,258.16, which was the average monthly value of the debt, considering the last five years of the invoices issued by Companhia de Água e egativos da Paraíba (CAGEPA) against DAESA. Finally, it was found to take approximately twelve years, transferring this amortized amount, in equal installments, to the payment of water treated by CAGEPA. It is important to state that, although the limitations on the collection of information, it is possible to import the proposal into the DESA, correcting the current flaws in economic-financial sustainability.